SSR-MARKERS OF RICE RESISTANCE TO THE TOTAL FLOODING - A. V. Azarin; A. V. Usatov; P. I. Kostylev; M. S. Makarenko; A. A. Kovalevich (Зерновое хозяйство России)
The present work deals with the study of the SSR-markers informativeness, associated with the locus of resistance to flooding Sub1A, to introduce this locus into the genotypes of highly productive varieties of domestic breeding. The SSR-analysis of the rice samples according to 7 micro satellite markers (RM 219, RM 316, RM 444, RM 464, RM 7481, RM 8303, RM 23877) showed that the marker RM 7481 gave the special and well-produced ranges, and was informative for the identification of the locus Sub1A. The hybridization among the donors of the locus of resistance to flooding BR-11, Inbara-3, CR-1009, TDK-1 and the early maturing Russian variety ‘Novator’ has been carried out to estimate the relationship of the inheritance of RM 7481 marker and the trait of resistance to flooding. The DNA-analysis of the hybrid F2 revealed the samples with the different allele variants of the locus Sub1A, the part of them has been found homozygous. The assessment of the resistance to water stress of rice hybrids and their parental forms in 21-day germination and the data of the molecule-genetic analysis showed that the increased water level significantly reduced this index of the variety ‘Navator’ and of the hybrids which did not inherit the locus of resistance. The lines-donors of the resistance and hybrid plants, which possess the locus Sub1A in homozygous and heterozygous states turned to be the most resistant forms according to the survival index. Thus, the study of SSR-markers connected with the locus of resistance Sub1A showed the high informativeness of co-dominant marker RM 7481 for the marker-associated breeding of the rice forms resistant to total flooding.